Study on combustion and emissions of a hydrous ethanol/gasoline dual fuel engine with combined injection. (1st February 2022) - Li, Decheng; Yu, Xiumin; Du, Yaodong; Xu, Mingjia; Li, Yinan; Shang, Zhen; Zhao, Zhe
Highlights: The HEDI + GPI combined injection mode was proposed. Larger ω prolonged CA 0-10 and CA 10-90, decreased Tmax and Pmax. HEDI + GPI mode had better power performance than GPI and EDI + GPI mode. ω of 5% is best for CO and NOx emissions, 10% is best for PN emissions. Larger ω increased HC emissions and made the size of particles smaller. Abstract: Hydrous ethanol has lower cost and energy consumption during the production process than anhydrous ethanol. Many researchers used hydrous ethanol instead of anhydrous ethanol to manufacture hydrous ethanol-gasoline. The water ratio in hydrous ethanol (ω) determines the energy consumption in the production process of ethanol. However, no one researched the effects of different ω on combustion and emissions of hydrous ethanol-gasoline. So, we prepared five kinds of ethanol with different ω (0, 5%, 10%, 15%, 20% vol.) to research the effects of ω on combustion and emissions. This study adopted combined injection with hydrous ethanol direct injection plus gasoline port injection (HEDI + GPI). The engine speed was 1500 rpm, and λ was 1, the intake manifold absolute pressure was 48 kPa, the direct injection ratio was 20%, five spark timings varied from 5 °CA BTDC to 25 °CA BTDC. The results showed hydrous ethanol prolonged flame development and propagation duration, decreased Tmax and Pmax, delayed APmax. Water increased COVimep, but using hydrous ethanol at the reasonable spark timing would not significantly affect the stability. Meanwhile, when the spark timing was MBT, compared with GE (gasoline/anhydrous ethanol dual fuel) fuel, as ω in GEW (gasoline/hydrous ethanol dual fuel) fuels increased, torque and brake thermal efficiency improved by 1.69%, 1.13%, −0.01%, −0.77%; HC increased by 2.13%, 9.02%, 23.89%, 37.15%; CO decreased by 41.95%, 28.56%, 5.59%, 2.46%; NOx decreased by 10.10%, −0.75%, −0.17%, 4.18%; total PN emissions decreased by 24.07%, 69.57%, 36.34%, 32.45%. Meanwhile, more water caused the size of particles to drop, made particles smaller.